Hubungan Status Gizi Dengan Kejadian Amenorea Pada Siswi Smp Negeri 1 Pademawu - Sitti Rohmah; Yulia Paramit Rusadi Rusadi (Universitas Islam Madura, 2021)
According to the East Java Provincial Health Office, the incidence of amenorrhoea from 1,600 adolescents who experienced amenorrhoea reached 170 (10%) adolescents, especially in several public and private schools. Food consumption affects a person's nutritional status. Nutritional status greatly affects menstrual function so that amenorrhea occurs. Based on a survey conducted as a preliminary study on February 14 at SMP Negeri 1 Pademawu on 10 students, 7 (70%) of them had amenorrhea. Several factors cause amenorrhoea, namely internal factors and external factors. Internal factors such as reproductive organs, hormones and disease. External factors such as nutritional status and lifestyle. The purpose of this study was to determine the relationship between nutritional status and the incidence of amenorrhea in students of SMP Negeri 1 Pademawu Class VIII. The design of this research is correlation analytic and based on time this research uses cross sectional. The population is all students of class VIII as many as 63 students taken by probability sampling technique with simple random sampling of 55 students. The results of the statistical test of the Contingency Coefficient using the SPSS 18 for windows program obtained the value of = 0.05, df = 2 X2 count (19.802), X2 table (5.99) which is 19.802> 5.99, thus it can be concluded that H0 is rejected and H1 was accepted, which indicated that there was a moderate relationship between nutritional status and the incidence of amenorrhea in class VIII students of SMP Negeri 1 Pademawu. Efforts that must be made for adolescent students are to enrich their knowledge about amenorrhea and nutritional status which can be accessed through print or electronic media and even from health workers. In addition, the school also cooperates with local health agencies to hold activities such as KRR in schools.